Penerapan Knowledge Sharing Pada Sektor Publik: Perspektif Bibliometrik - Retno Andini; Tamara Adriani Salim (Perpustakaan Nasional, 2024)
This study aims to investigate the research dynamics related to the Application of Knowledge Sharing in the Public Sector. The study was conducted in December 2023 by searching the Scopus database with the keywords